Latent Classes Among Recipients of a Brief Alcohol Intervention: A Replication Analysis. Issue 1 (2nd January 2016) - Cochran, Gerald; Field, Craig; DiClemente, Carlo; Caetano, Raul
Abstract : The purpose of this study was to identify differential improvement in alcohol use among injured patients following brief intervention. Latent class analysis was conducted to identify patient profiles based on alcohol-related risk from two clinical trials (Texas: N = 737; Maryland: N = 250) conducted in Level-1 trauma centers. Drinking was analyzed to detect improvements at 6 and 12 months. The four classes that emerged from Maryland participants were similar to four of the five classes from Texas. Increases in both studies for days abstinent were reported by classes characterized by multiple risks and minimal risks. Decreases in volume consumed for both studies were also reported by classes characterized by multiple risks and minimal risks. By classifying patients according to alcohol-related risk, providers may be able to build on positive prognoses for drinking improvements or adapt interventions to better serve those likely to improve less.